La presunción de inocencia y su contraposición con la prisión preventiva - Mena Morales, Freddy Iván (2015)
The research called: "The presumption of innocence and opposed to preventive detention," summarizes the legal situation that exists at present our country to defy the Supreme standard, as is the freedom of individuals when preventive detention is imposed when the guilt has not yet been fully proven. The framework has the legal and doctrinal support related to the main themes of study, such as the presumption of innocence. The methodological framework is contained in the mode that was done in the investigation, being mainly bibliographic field and the need to consult the criterion for legal professionals on the subject, as well as connoisseurs of Judges of matter over this research topic. The results allowed to see that in our country a statute overrides the Constitution. In conclusion the need to propose an answer to this problem is to implement same policy permanently to operators of justice on issues of constitutional law training was established.